Identification of Key Proteins and Networks Related to Grain Development in Wheat (Triticum aestivum L.) by Comparative Transcription and Proteomic Analysis of Allelic Variants in TaGW2-6A - Du, Dengfeng; Gao, Xin; Geng, Juan; Li, Qingyan; Li, Liqun; Lv, Qian; Li, Xuejun (Frontiers in Plant Science, 2016)
In wheat, coding region allelic variants of TaGW2-6A are closely associated with grain width and weight, but the genetic mechanisms involved remain unclear. Thus, to obtain insights into the key functions regulated by TaGW2-6A during wheat grain development, we performed transcriptional and proteomic analyses of TaGW2-6A allelic variants. The transcription results showed that the TaGW2-6A allelic variants differed significantly by several orders of magnitude. Each allelic variant of TaGW2-6A reached its first transcription peak at 6 days after anthesis (DAA), but the insertion type TaGW2-6A allelic variant reached its second peak earlier than the normal type, i.e., at 12 DAA rather than 20 DAA. In total, we identified 228 differentially accumulated protein spots representing 138 unique proteins by two-dimensional gel electrophoresis and tandem MALDI-TOF/TOF-MS in these three stages. Based on the results, we found some key proteins that are closely related to wheat grain development. The results of this analysis improve our understanding of the genetic mechanisms related to TaGW2-6A during wheat grain development as well as providing insights into the biological processes involved in seed formation.